1.7 micron optical coherence tomography for vaginal tissue characterization in vivo. Issue 2 (30th July 2018) - Li, Yan; Sudol, Neha T.; Miao, Yusi; Jing, Joseph C.; Zhu, Jiang; Lane, Felicia; Chen, Zhongping
Abstract : Objectives: Optical coherence tomography (OCT) can noninvasively visualize in vivo tissue microstructure with high spatial resolution that approaches the histologic level. Currently, OCT studies in gynecology are few and limited to a conventional 1.3 μm center wavelength swept light source which provides high spatial resolution but limited penetration depth. Here, we present a novel endoscopic OCT system with improved penetration depth and high resolution. Methods: A novel endoscopic OCT system was developed based on a 1.7 µm swept source laser, which is capable of deeper tissue penetration due to its longer wavelength. To evaluate the performance of system, we imaged the human vaginas in vivo with both conventional 1.3 and 1.7 μm endoscopic OCT systems. Results: With the 1.7 μm endoscopic OCT system, imaging depth was improved by more than 25%, allowing better visualization of the lamina propria and clear contrast of the epithelial layer from the surrounding tissues. Conclusion: The significantly improved performance of the novel 1.7 μm OCT imaging system demonstrates its potential use as a minimally‐invasive monitoring tool of vaginal health in gynecologic practice. Lasers Surg. Med. 51:120–126, 2019. © 2018 Wiley Periodicals, Inc.